Does Social Trust Speed up Reforms? The Case of Central-Bank Independence - Niclas Berggren; Sven-Olov Daunfeldt; Jörgen Hellström (Research Institute of Industrial Economics (IFN), 2015)
Many countries have undertaken central-bank independence reforms, but the years of implementation differ. What explains such differences in timing? This is of interest more broadly, as it sheds light on factors that matter for the speed at which economic reforms come about. We study a rich set of potential determinants, both economic and political, but put special focus on a cultural factor, social trust. We find empirical support for an inverse u-shape: Countries with low and high social trust implemented their reforms earlier than countries with intermediate levels. We make use of two factors to explain this pattern: the need to undertake reform (which is more urgent in countries with low social trust) and the ability to undertake reform (which is greater in countries with high social trust).
Keywords: E52; E58; P48; Z13; 330; Central banks; Independence; Social trust; Inflation; Monetary policy; Reform